Another economic miracle? The German labor market and the great recession - Ulf Rinne; Klaus F. Zimmermann (IZA Journal of Labor Policy, 2012)
Germany's labor market responded only mildly to the Great Recession. Important factors for this development include the strong economic position due to recent labor market reforms, the crisis affecting mainly export-oriented companies, the extension of short-time work, time buffers due to working time accounts, the behavior of social partners, and automatic stabilizers. We emphasize the important interaction between short-time work and long-term shortages of skilled workers in sectors particularly affected by the crisis. Although Germany's experience is in stark contrast to the United States, we identify and discuss common challenges at the center of the future jobs debate.
Keywords: J68; J21; P52; O57; 330; economic crisis; Germany; short-time work; unemployment; labor market institutions; internal flexibility; Wirtschaftskrise; Arbeitslosigkeit; Arbeitsmarktflexibilität; Unterbeschäftigung; Fachkräfte; Deutschland